2014
DOI: 10.7554/elife.02564
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo effector Yorkie activates transcription by interacting with a histone methyltransferase complex through Ncoa6

Abstract: The Hippo signaling pathway regulates tissue growth in Drosophila through the transcriptional coactivator Yorkie (Yki). How Yki activates target gene transcription is poorly understood. Here, we identify Nuclear receptor coactivator 6 (Ncoa6), a subunit of the Trithorax-related (Trr) histone H3 lysine 4 (H3K4) methyltransferase complex, as a Yki-binding protein. Like Yki, Ncoa6 and Trr are functionally required for Hippo-mediated growth control and target gene expression. Strikingly, artificial tethering of Nc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 30 publications
(47 reference statements)
4
60
0
Order By: Relevance
“…NCOA6 is a common coactivator (107) and has been demonstrated to be essential for embryo development and survival through knock-out studies in mice (108e110). The Drosophila NcoA6 gene has also been shown to be important for viability and proper tissue development through interaction with the Yorkie/YAP transcriptional activator involved in the Hippo signaling pathway (111,112). NCOA6 has been shown to associate with a large variety of nuclear hormone receptors, including prostanoid, retinoid, vitamin D3, thyroid hormone, and steroid receptors in humans, enhancing the activating ability of these transcription factors.…”
Section: Components Of the Human Kmt2c/kmt2d Compass-like Complexesmentioning
confidence: 97%
“…NCOA6 is a common coactivator (107) and has been demonstrated to be essential for embryo development and survival through knock-out studies in mice (108e110). The Drosophila NcoA6 gene has also been shown to be important for viability and proper tissue development through interaction with the Yorkie/YAP transcriptional activator involved in the Hippo signaling pathway (111,112). NCOA6 has been shown to associate with a large variety of nuclear hormone receptors, including prostanoid, retinoid, vitamin D3, thyroid hormone, and steroid receptors in humans, enhancing the activating ability of these transcription factors.…”
Section: Components Of the Human Kmt2c/kmt2d Compass-like Complexesmentioning
confidence: 97%
“…Many genes are transcriptionally activated by TEAD complexed with YAP and/or TAZ (Zhu et al 2015). Mechanistically, YAP and TAZ stimulate TEAD transcriptional activity by recuriting components of the SWI/SNF chromatin remodeling complex or NCOA6 histone methyltransferase complex (Oh et al 2013(Oh et al , 2014Qing et al 2014;Skibinski et al 2014). Interestingly, the YAP/TAZ-TEAD complex can also operate as transcriptional corepressors by recruiting the NuRD histone deacetylate complex for additional target genes, such as DDIT4 and Trail regulation.…”
Section: The Yap/taz Transcriptional Programs and Their Functional Oumentioning
confidence: 99%
“…Back in 2005, it was proposed that TAZ can associate with histone acetyltransferases p300 and PCAF, and dramatically activates TBX5-dependent promoters, but whether YAP has the same activity has not been confirmed [118]. Moreover, it was recently reported that Yki regulates transcription through WW domain-mediated interaction with NcoA6 (a subunit of the Trr methyltransferase complex) and then modification of local chromatin [145,146]. NcoA6 is required for Yki/Sd-induced tissue overgrowth.…”
Section: Mechanisms Of Yap In Transcription Activationmentioning
confidence: 99%